[PP.34.37]: ACTIVITY OF BRAIN AND SERUM ANGIOTENSIN CONVERTING ENZYME 2 IS ALTERED IN THE ACUTE PHASE OF RAT AND HUMAN ISCHEMIC STROKE. (June 2015) - Bennion, D.; Haltigan, E.; Irwin, A.; Rosado, C.; Purich, D.; Waters, M.; Sumners, C.
Abstract : Objective: The angiotensin converting enzyme 2/angiotensin-(1-7) [ACE2/Ang-(1-7)] axis represents a promising target for inducing stroke neuroprotection. Here, our primary objective was to assess the effects of ischemic stroke on endogenous ACE2 activity in rat serum and brain, and in human serum, after ischemic stroke. We further explored the effects of inhibition of endogenous brain ACE2 activity on the severity of ischemic stroke in rats, to further validate ACE2 as a potential stroke neuroprotective target. Design and method: Serum samples were collected from Sprague Dawley rats that underwent endothelin-1 induced middle cerebral artery occlusion, or from ischemic stroke patients and age-matched controls within four hours (h) and again at three days (d) after stroke onset. Brain (cerebral cortex) samples were also collected from the rats at the same time points. ACE2 activity was assessed by fluorometric assay. Separately, the ACE2 inhibitor (MLN-4760; 50 pmol/uL/h) was infused into the cerebral ventricles of rats for 5d before and 3d after stroke when neurological function and infarct volume were measured. All animal and human experiments were approved by Institutional Review Committees. Raw ACE2 activity data were presented as % changes in activity vs. controls. Results: Ischemic stroke in rats resulted in an initial decrease in serum ACE2 activity at 4 h after stroke (66.2 ± 4.7%, n = 44) vs. pre-stroke levels (100 ± 6.6%, n = 45), followed by a rebound at 3d post-stroke (107.2 ± 15.1%, n = 11). These findings were recapitulated in samples from human stroke, where serum ACE2 activity was decreased at ∼4 h after stroke (51.2 ± 7.6%, n = 8) as compared to healthy controls (100 ± 14.7%, n = 9), followed by rebound at 3d post-stroke (84.14 ± 23.12%). In contrast, ACE2 activity within the cerebral cortex of rats ipsilateral to the stroke was significantly elevated 4 h after stroke, but returned to control values within 3d. Lastly, central administration of MLN-4760 into rats resulted in significantly worse neurological function at 4 h and at 3d post ischemic-stroke. Conclusions: Our findings suggest that stroke therapeutics that target the ACE2/Ang-(1-7)/Mas axis may interact cooperatively with endogenous stroke-induced changes in this enzyme, lending promise to their further study as potential neuroprotective agents.